2014
DOI: 10.1002/glia.22774
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in spinal cord injury: Phenotypic and functional change from exposure to myelin debris

Abstract: Macrophage activation and persistent inflammation contribute to the pathological process of spinal cord injury (SCI). It was reported that M2 macrophages were induced at 3–7 days after SCI but M2 markers were reduced or eliminated after 1 week. By contrast, M1 macrophage response is rapidly induced and then maintained at injured spinal cord. However, factors that modulate macrophage phenotype and function are poorly understood. We developed a model to distinguished bone marrow derived macrophages (BMDMs) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
267
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(278 citation statements)
references
References 74 publications
(98 reference statements)
8
267
0
3
Order By: Relevance
“…Therefore, these results confirm that CCR2-expressing cells are increased in the ipsilateral ventral but not dorsal horn at POD 7 after SNT. Finally, to determine whether CCR2 RFP/+ monocytes have the ability to enter the spinal dorsal horn, we used a well-established mouse contusion model of spinal cord injury (SCI) (Wang et al, 2015) in CCR2 RFP/+ :CX3CR1 GFP/+ mice. Indeed, we found numerous CCR2 RFP/+ monocytes in spinal dorsal horn 7 days after SCI (Figure S2a).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these results confirm that CCR2-expressing cells are increased in the ipsilateral ventral but not dorsal horn at POD 7 after SNT. Finally, to determine whether CCR2 RFP/+ monocytes have the ability to enter the spinal dorsal horn, we used a well-established mouse contusion model of spinal cord injury (SCI) (Wang et al, 2015) in CCR2 RFP/+ :CX3CR1 GFP/+ mice. Indeed, we found numerous CCR2 RFP/+ monocytes in spinal dorsal horn 7 days after SCI (Figure S2a).…”
Section: Resultsmentioning
confidence: 99%
“…55 Myelin debris may be an associated factor switching the macrophage phenotype from M2 to M1. 56 In addition, ROS are involved in the activation process of M1 macrophages partly by nuclear factor-kappa light-chain-enhancer of activated B cells (NF-kB) pathway. It still needs further study to understand how ROS, resulting from SCI, regulate the polarization of macrophages.…”
mentioning
confidence: 99%
“…Accordingly, current study cannot differentiate whether the observed changes of polarization primarily occurred in which cell population. Future double‐staining study that use antibodies specific to microglia, such as P2Y12 and TMEM119(Bennett et al, ; Gu et al, ; Tatsumi et al, ; Wang et al, ) may allow identifying the specific cell population and quantifying the relative proportion of microglia versus macrophages that are modulated by melatonin treatment after SCI. Microglia/macrophages have been broadly categorized into two distinct states as either classically activated (M1) or alternatively activated (M2) state(Colonna & Butovsky, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Future double‐staining study that use antibodies specific to microglia, such as P2Y12 and TMEM119(Bennett et al, ; Gu et al, ; Tatsumi et al, ; Wang et al, ) may allow identifying the specific cell population and quantifying the relative proportion of microglia versus macrophages that are modulated by melatonin treatment after SCI. Microglia/macrophages have been broadly categorized into two distinct states as either classically activated (M1) or alternatively activated (M2) state(Colonna & Butovsky, ; Wang et al, ). Although this M1/M2 paradigm is helpful for conceptualizing microglia/macrophages activities in vitro, recent studies suggested that the spectrum of microglia/macrophages activation in vivo is likely a continuum of different phenotype states (Colonna & Butovsky, ; Morganti, Riparip, & Rosi, ).…”
Section: Discussionmentioning
confidence: 99%